Bipolar Disorder: What Can Psychotherapists Learn From the Cognitive Research? - Johnson, Sheri (2007)
Randomized controlled trials of psychological treatment, principally cognitive therapy, for bipolar disorder have yielded inconsistent results. Given the status of this evidentiary base, we provide a more fine-grained analysis of the cognitive profiles associated with bipolar disorder to inform clinical practice. In this practice-friendly review, we consider evidence that both negative and positive cognitive styles are related to bipolar disorder. Cross-sectional and prospective evidence suggest that negative cognitive styles are related to depression within bipolar disorder, but there also is evidence that bipolar disorder is related to an elevated focus on goals as well as to increases in confidence during manic states. With such findings as backdrop, we consider the outcomes of psychological treatments for bipolar disorder and advance several suggestions for clinical practice.